(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
The utilization of multimedia technology has given positive contributions in the implementation of teaching listening. It provides the teachers with easier and more efficient ways to facilitate listening materials and practices in the form of audio as the main important sources. However, employing audio only is considered to be not enough to assist students to comprehend the information well. The use of audio-visual materials such as videos is proposed as a better means to acquire students’ listening comprehension. The visualization of videos provides the students the ease to get better contexts, decrease the boredom, and stimulate the imagination to the more authentic situation. This paper employed causal comparative research to examine the use of audio and audiovisual materials in teaching listening, then to evaluate which one has a better result in obtaining students’ listening comprehension as viewed from genders. Keywords: video, listening comprehension, gender